The Influence of Social Networking on Lifestyle: A Higher Education Perspective - Veerasamy, D (Journal of Education and Vocational Research, 2013)
Social networks have become a way of life for many people who use them to connect and communicate with the world at large. Social media is defined as any tool or service that uses the Internet to facilitate conversations. Facebook is one of the most popular social networking sites (SNSs) and has a total of 55 million active users worldwide with an average of 250000 new registrations per day. After Yahoo, MySpace and Google, Facebook is also the fourth most popular SNS in South Africa. The purpose of the paper was to determine whether social networks have an influence on higher education students’ lifestyles and behaviour. This research was descriptive and quantitative in nature. The sample comprised 386 students studying at the Durban University of Technology (DUT). The results indicated that the majority of the respondents preferred Facebook as their social network of choice. More than half of the respondents indicated that they access their preferred social network five times or more per day. The majority of the respondents agreed that social networks allow for global interaction and that maintaining relationships has become easier with social networking,